METEOR cruise M146 raw data of EM122 multibeam echosounder (bathymetry, beam time series), Tropiquito - Klügel, Andreas; Römer, Miriam; Wintersteller, Paul (MARUM - Center for Marine Environmental Sciences, University Bremen, 2018)
Multibeam echosounder (MBES) data recorded during RV METEOR cruise M146 between 17.03.2018 and 16.04.2018. The data covers the transit (cruise started in Receive/Brazil) in international waters crossing the Atlantic Ocean, a single survey line crossing Tropiquito seamount (SW of Tropic seamount) and the main target at Henry seamount, southeast of El Hierro, Canary Islands. The main objective of this cruise was to discover hydrothermal venting sites at Henry Seamount as data acquired during the previous cruise M66/1 showed evidences that there might be active hydrothermal circulation at Henry Seamount. Therefore, the bathymetric surveys conducted with hull-mounted MBES and the MARUM AUV SEAL were accompanied with investigations in the water column, heat flow measurements, TV-sled dives and high-resolution reflection seismic. CI Citation: Paul Wintersteller (seafloor-imaging@marum.de) as responsible party for bathymetry and backscatter post-processing and its products. Description of the data source: During the RV METEOR cruise M146 the Kongsberg EM122 multibeam echosounder with a nominal sounding frequency of 11.5 to 12.5 kHz was utilized. 288 beams (and up to 864 soundings in equidistant and dual swath mode) are formed for each ping with a 1°(Tx)/2°(Rx) footprint while the seafloor is detected using amplitude and phase information for each beam sounding. For further information consult https://www.km.kongsberg.com/. The EM122 was recording constantly within the permitted areas, either designated to bathymetry surveys or flare imaging-surveys. In total, three different subsets of hydroacoustic data were acquired: a transatlantic dataset covering the transit in international waters; a second dataset covering the area of Tropiquito Seamount, which is situated about 100 km southwest of Tropico seamount and the main dataset of the area of Henry Seamount, which is located roughly 40 km southeast of El Hierro (Canary Islands). Responsible person during this cruise / PI: Miriam Römer (mroemer@marum.de) & Paul Wintersteller (pwintersteller@marum.de) Chief Scientist: A. Klügel (akluegel@uni-bremen.de) CR: not yet available CSR: not yet available A special thanks goes to the watch keeper during M146: Anna Katharina Bachmann, Rachel Barrett, Philipp Held, Kai Frederik Lenz, Katja Lindhorst, Anne-Christin Melcher, Laura Kramer, Nikolas Stange, Anne Strack.